PENGEMBANGAN PRODUK UNGGULAN KELOMPOK EKONOMI KREATIF PUSAKA DENGAN METODE COCHRAN, AHP, DAN SWOT DI KABUPATEN CIAMIS - MAMAN HILMAN MAMAN; Eky Aristriyana (Universitas Widyatama, 2023)
Small businesses in the Pusaka Creative Economy Group are experiencing quite good growth, but so far the type of business that is a superior product has not been identified. So it is difficult to carry out development because it has not focused on one type of business. This study aims to determine the types of superior products in the Heritage Creative Economy Group and their development strategies. The methods used are Cochran (Q Test), AHP, and SWOT. The research results obtained priority with a weight value of 0.44064, namely Jiwel Food Products are superior products. Meanwhile, based on the results of the SWOT analysis, the strategy for developing Jiwel Food Products is a Progressive Strategy, namely the company is in prime and steady condition, so it is possible to develop and grow the company.